Indigenous Non-Saccharomyces Yeasts With β-Glucosidase Activity in Sequential Fermentation With Saccharomyces cerevisiae: A Strategy to Improve the Volatile Composition and Sensory Characteristics of Wines - Gao, Pingping; Peng, Shuai; Sam, Faisal Eudes; Zhu, Yatong; Liang, Lihong; Li, Min; Wang, Jing (Frontiers in Microbiology, 2022)
Non-Saccharomyces (NS) yeasts with high β-glucosidase activity play a vital role in improving the aroma complexity of wines by releasing aroma compounds from glycosidic precursors during fermentation. In this study, the effect of sequential inoculation fermentation of Meyerozyma guilliermondii NM218 and Hanseniaspora uvarum BF345 with two Saccharomyces cerevisiae strains (Vintage Red (VR) and Aroma White (AW)) on volatile compounds and sensory characteristics of wines was investigated. Prior to winemaking trials, the sequential inoculation times of the two NS yeasts were evaluated in synthetic must, based on changes in strain population and enzyme activity. The intervals for inoculation of NM218 and BF345 with the S. cerevisiae strains were 48 and 24 h, respectively. In the main experiment, sequential inoculation fermentations of the two strains with S. cerevisiae were carried out in Cabernet Sauvignon (CS) and Chardonnay (CH) grape must. The oenological parameters, volatile composition, and sensory characteristics of the final wines were assessed. No clear differences were observed in the oenological parameters of the sequentially fermented CH wines compared with the control, except for residual sugar and alcohol. However, in CS wines, the total acid contents were significantly lower in the wines fermented by sequential inoculation compared to the control. Both NM218 and BF345 improved the aroma complexity of wines by increasing esters and terpenes when inoculated with S. cerevisiae strains compared to inoculation with S. cerevisiae strains alone. NM218 resulted in a more positive effect on CS wine aroma, with higher levels of citronellol and trans-nerolidol. BF345 significantly enhanced the floral and fruity aromas of CH wine by producing higher concentrations of geranyl acetone, β-damascenone, trans-nerolidol, and nerol. Both NM218 and BF345 yeasts could potentially be used to improve wine aroma and overall quality, especially wine floral and fruity aromas, when used in sequential inoculation with S. cerevisiae.